2007
DOI: 10.1042/cs20060050
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers increase with severity of upper-extremity overuse disorders

Abstract: MSDs (musculoskeletal disorders) from overuse are common occupational health problems that cause pain, functional loss and loss of work time. The aim of the present study was to determine whether a relationship exists between the severity of early-onset overuse-related MSDs of the upper extremity and serum levels of IL-1beta (interleukin-1beta), TNF-alpha (tumour necrosis factor-alpha), IL-6 (interleukin-6) and CRP (C-reactive protein). Twenty-two subjects with upper-extremity MSDs due to overuse for no longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
97
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 45 publications
(76 reference statements)
7
97
3
1
Order By: Relevance
“…overuse injuries. 10 In contrast to our human study, we did not find increased serum IL-6 in this study, a result consistent with findings of a repetitive pinching task in a nonhuman primate model 6 and a study examining patients with carpal tunnel syndrome. 19 However, there was no detectable serum TNFa in those two studies 6,19 results differing from ours.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…overuse injuries. 10 In contrast to our human study, we did not find increased serum IL-6 in this study, a result consistent with findings of a repetitive pinching task in a nonhuman primate model 6 and a study examining patients with carpal tunnel syndrome. 19 However, there was no detectable serum TNFa in those two studies 6,19 results differing from ours.…”
Section: Discussioncontrasting
confidence: 57%
“…Although several studies have found increased serum biomarkers of injury, inflammation, or collagen turnover in patients with repetitive motion injury or following performance of repetitive tasks, 2,10,19,20 this is the first study to report the presence of chemokines in serum following performance of repetitive upper extremity tasks and to examine such a large panel of cytokines and chemokines in RMI. We have previously reported that performance of the HRNF task leads to increased serum IL-1a, results confirmed here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37 Evidence from both an animal injury model 38 and human study of pulmonary dysfunction 39 indicates that higher levels of TNF-α may influence the recovery of muscle function. On the contrary, others have demonstrated increased levels of serum TNF-α in tandem with higher levels of disability in chronic low back pain, 40 upper extremity overuse injuries, 41 and significant losses of muscle mass in patients with cancer, AIDS and chronic obstructive pulmonary disease. 42 Further study investigating the directional influence of local inflammatory factors on muscle structure and function following whiplash is warranted and well underway.…”
Section: Discussionmentioning
confidence: 99%